STRATEGI PENGEMBANGAN WISATA BAHARI DI PANTAI KETAPING - Ramadi, Muhammad; Asnur, Lise (Jurnal Daya Saing, 2024)
This research was motivated by the researcher’s observations regarding the Marine Tourism Development Strategi at Ketaping beach, Batang Anai District, Padang Pariaman Regency. Maritime Tourism Development can be described by reviewing and fulfilling the indicators (Attraction, Accessibilities, Accommodation, and Ancilary Service), and assisted by SWOT Analysis. This type of research is descriptive qualitative research. The data collection technique was carred out using observation, interviews, and dokumentation methods. Determining the research informants using a purposive sampling technique consisted of the Head of the Nagari Village, The Ketaping Beach Community and Visitors. The results of the research found that there are several potentials, namely (1) Tourist attractions: it has beautiful natural landscapes and agro tourism areas which can be used to increase the APBD for the Ketaping Beach area. (2) Accessibility: lack of public transportation to and from Ketaping Beach. (3) Accommodation: additional core accommodation such as accommodation, health facilities and restaurants. (4) Supporting Services: periodic maintenance of toilets, prayer rooms and parking areas. Keywords: